A case of iatrogenic Cushing syndrome and subsequent adrenal insufficiency from a hidden ingredient in the supplement Artri Ajo King - Ana Carolina Boncompagni; Erin Ruiz; Ashley C. Rider (Journal of the American College of Emergency Physicians Open)
Abstract Dietary supplement use is common in the United States. Supplements are regulated by the US Food and Drug Administration (FDA) under a separate set of guidelines from typical food and drug products. This case report describes a patient who presented to the emergency department (ED) with abdominal pain, vomiting, and generalized weakness. On detailed history, we learned that he had been taking a supplement called Artri Ajo King for 18 months, followed by recent abrupt cessation before his ED presentation. He was subsequently found to have a low serum cortisol level and was diagnosed with secondary adrenal insufficiency by a cosyntropin stimulation test. Ultimately, he was started on hydrocortisone with resolution of his symptoms. This case illustrates the consequence of allowing dietary supplements to be sold before FDA evaluation as well as the importance of physicians eliciting history of supplement use and offering a culturally competent discussion with their patients regarding supplement use.